Thulium Oxide Nanoparticles: A new candidate for image-guided radiotherapy. (14th June 2018) - Engels, Elette; Westlake, Matt; Li, Nan; Vogel, Sarah; Gobert, Quentin; Thorpe, Nathan; Rosenfeld, Anatoly; Lerch, Michael; Corde, Stéphanie; Tehei, Moeava
Abstract: Nanoparticles, with their distinct properties that vary from their bulk material equivalent, continue to gain popularity for studies into multi-modal applications in medicine. This research introduces the use of thulium oxide nanoparticles for biological applications and characterizes the potential of this novel nanoparticle for image-guided radiotherapy of brain cancer. In this study, we investigate the structural characteristics of this nanoparticle, and reveal a significant dose enhancement towards radioresistant brain tumour cells in vitro that also underlies an improvement in the CT image contrast of brain tumours in vivo . The thulium oxide nanoparticles utilized in the investigations described in this article were measured to be 40–45 nm from x-ray diffraction and scanning electron microscopy data. In vitro investigations assessed the cell survival and DNA damage in 9 l gliosarcoma cells following irradiation with 150 kVp orthovoltage x-rays. Immediately after the 150 kVp irradiation (15 min) an increase in the number of γ -H2AX induced foci indicates the production of more double-strand DNA breaks. Following from the short time-frame irradiation outcomes, clonogenic cell survival assays confirmed long-term radio-sensitization, with the cell sensitivity increasing by a factor of 1.32 (measured at the 10% survival fraction) for the irradiated 9 l cells exposed to thulium nanoparticles. A simple CT experiment shows that our thulium nanoparticles suspended in water at concentrations >0.5 mg ml −1 (0.05–20 mg ml −1 investigated) are clearly observable against water. Extending the CT experiment to an in vivo investigation, cellular uptake of the nanoparticles was demonstrated through CT image enhancement of the cancer site in 9- to 10-week-old Fisher rats bearing 9 l gliosarcomas, 12 days after cell implantation. The 9 l cancer is clearly visible on the CT image after injecting 40 μ g of nanoparticles (2 μ l at 20 mg ml −1 ) directly to the cancer site (5.5 mm from the dura and 3.5 mm right laterally of the bregma, 5 mm depth). To our knowledge, this work demonstrates the first application of thulium nanoparticles in biology and medicine, for radiotherapy and image guidance purposes